Low microzooplankton grazing rates in the Arctic Ocean during a Phaeocystis pouchetii bloom (Summer 2007): fact or artifact of the dilution technique? - Calbet, Albert; Saiz, Enric; Almeda, Rodrigo; Movilla, Juan Ignacio; Alcaraz, Miquel (Journal of Plankton Research, 2010)
We studied the structure and dynamics of the microbial community of Arctic waters during July 2007 using a microzooplankton grazing dilution approach. The sampling covered a latitudinal transect along the East Greenland Sea, and a series of stations in the high Arctic (up to 80°50′N), west and north of the Svalbard Islands. A main feature of the area was the presence of Phaeocystis pouchetii , which formed dense blooms. Despite the considerable biomass of microzooplankton (mostly large ciliates and dinoflagellates), their grazing impact on phytoplankton, assessed as total chlorophyll a, was significant in only 6 out of 16 experiments, which resulted in 8% of the standing stock being consumed on average. Overall, phytoplankton instantaneous growth rates were very low and even negative at times (range: −0.24 to 0.14; average: −0.04 for total chlorophyll), which could not be attributed to nutrient limitation nor the estimated microzooplankton grazing. We present three non-exclusive explanations for this fact: (i) we were facing a senescent community in which many organisms were dying either as a result of virus infections or for other natural causes, as corroborated by parallel estimates of natural cell mortality using membrane permeability probes; (ii) the widespread and abundant P. pouchetii was probably deterring grazing and adversely affecting the entire planktonic community at the time of the study; and (iii) the dilution technique failed to give a real estimate of grazing (i.e. either non- significant or positive slopes), likely as a consequence of trophic cascades (decline of major grazers in the more concentrated treatments) combined with saturated-feeding responses. This last point calls for special attention when intending to use the dilution technique in productive environments, where grazing may be saturated.